Relatively Early and Late-Onset Neuromyelitis Optica Spectrum Disorder in Central China: Clinical Characteristics and Prognostic Features - Yu, Jinbei; Yan, Shuai; Niu, Pengpeng; Teng, Junfang (Frontiers in Neurology, 2022)
Background We aimed to analyze the clinical characteristics and prognostic features of Chinese patients with relatively late-onset neuromyelitis optica spectrum disorder (RLO-NMOSD>40 years of age at disease onset), compared with patients with relatively early onset NMOSD (REO-NMOSD, ≤ 40 years of age at disease onset). Methods We retrospectively reviewed the medical records of patients with NMOSD in central China (with disease courses longer than 3 years) between January 2012 and January 2021. We further analyzed the clinical and prognostic differences between patients with REO-NMOSD and RLO-NMOSD. Results A total of 71 patients were included in this study. The results showed that 39 (54.9%) of the patients had RLO-NMOSD. The patients with RLO-NMOSD had higher expanded disability status scale (EDSS) scores than patients with REO-NMOSD at the initial (5.0 vs. 3.0, p = 0.01), 3-month (4.0 vs. 2.5, p = 0.001), 1-year (4.0 vs. 2.5, p = 0.003), 3rd-year (3.5 vs. 3.0, p = 0.0017), and final follow-up (4.0 vs. 2.5, P = 0.002) time points. The EDSS scores of visual function were 2.0 (1.0–3.0) in REO-NMOSD and 3.0 (2.0–3.0) in RLO-NMOSD (p = 0.038) at the final follow-up time point. The locations of spinal cord lesions at transverse myelitis (TM) onset were prone to cervical cord in patients with REO-NMOSD. There were no between-group treatment differences. The risk of requiring a cane to walk (EDSS score of 6.0) increased as the age of disease onset increased: for every 10-year increase in the age of disease onset, the risk of needing a cane to walk increased by 65% [hazard ratio (HR) = 1.65, 95% CI 1.15–2.38, p = 0.007]. Another significant predictor identified in the multivariate analysis was annualized relapse rate (ARR) (HR = 2.01, 95% CI 1.09–3.71, p = 0.025). In addition, we observed a positive correlation between age at onset and EDSS scores at the final follow-up (Spearman's r = 0.426, p < 0.0001) time point. EDSS scores at different periods were significantly different between patients with RLO-NMOSD and REO-NMOSD with anti-aquaporin-4 (AQP4) IgG positive. Conclusion The patients with RLO-NMOSD developed more severe disabilities than patients with REO-NMOSD at a variety of time periods. All of the patients may experience recurrent aggravated symptoms after their first year, with only patients with REO-NMOSD partly recovering from the 3rd year. The age at onset and ARR were the main predictors of outcomes.